2016
DOI: 10.1001/jamainternmed.2016.6721
|View full text |Cite
|
Sign up to set email alerts
|

Association of Industry Sponsorship With Outcomes of Nutrition Studies

Abstract: IMPORTANCE Food industry sponsorship of nutrition research may bias research reports, systematic reviews, and dietary guidelines.OBJECTIVE To determine whether food industry sponsorship is associated with effect sizes, statistical significance of results, and conclusions of nutrition studies with findings that are favorable to the sponsor and, secondarily, to determine whether nutrition studies differ in their methodological quality depending on whether they are industry sponsored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 42 publications
5
42
0
5
Order By: Relevance
“…For example, evidence for substantial bias has been identified in industry sponsored research on health effects of sugar sweetened beverages3536 and artificial sweeteners 37. Evidence for bias in industry sponsored research on other nutritional topics is less strong, with a non-significant trend towards about 30% higher likelihood of favourable conclusions 38. This figure is similar to that found in analyses of industry sponsored studies of drugs or medical devices 39.…”
Section: Vested Interestsmentioning
confidence: 73%
“…For example, evidence for substantial bias has been identified in industry sponsored research on health effects of sugar sweetened beverages3536 and artificial sweeteners 37. Evidence for bias in industry sponsored research on other nutritional topics is less strong, with a non-significant trend towards about 30% higher likelihood of favourable conclusions 38. This figure is similar to that found in analyses of industry sponsored studies of drugs or medical devices 39.…”
Section: Vested Interestsmentioning
confidence: 73%
“…13 Existe evidencia sólida del estudio de estas relaciones que sugiere que la investigación patrocinada por la industria es susceptible de conferir sesgos a su favor en los resultados. [14][15][16] Este fenómeno ha hecho indispensable que los investigadores comuniquen con transparencia sus relaciones con la industria, para que puedan ser tomadas en cuenta al preparar investigaciones similares y controladas en síntesis de literatura, revisiones sistemáticas y metaanálisis. [17][18][19] Un reporte científico publicado recientemente ha causado gran preocupación al demostrar cómo la industria azucarera pudo sesgar la investigación en enfermedad cardiovascular, así como las recomendaciones y guías alimentarias en Estados Unidos, al haber patrocinado a investigadores que nunca declararon su CDI.…”
Section: Antecedentesunclassified
“…Very recently, Nicholas Chartres and colleagues published a systematic review and metaanalysis regarding association of industry sponsorship with outcomes of nutrition studies. 1 The authors included 12 reports and found one which examined effect sizes and concluded that studies sponsored by the food industry reported significantly smaller harmful effects for the association of soft drink consumption with energy intake and body weight than those not sponsored by the food industry. Also, 8 reports, including 340 studies, assessed the association of industry sponsorship with authors' conclusions.…”
Section: Dear Editormentioning
confidence: 99%
“…Based on the report by Chartres et al we have now compared the effects of nutritional therapy on outcomes in subgroups based on industry sponsorship using our 2016 metaanalysis dataset. 1 Based on the conflict of interest and funding statements included in the original publications, we found that out of 22 included trials 11 (50%) declared industry sponsoring or partial industry sponsoring, 8 (36%) declared non-industry sponsoring or no sponsoring and 3 (14%) did not disclose sponsorship ( Table 1). Our subgroup results indicate that there is no evidence for better results in trials with industry sponsoring compared with no-industry sponsoring ( Table 2).…”
Section: Dear Editormentioning
confidence: 99%